1984
DOI: 10.1007/bf03351023
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hemiagenesis in two sisters

Abstract: Two sisters with thyroid hemiagenesis are described. The patients presented diffuse thyroid enlargement of right lobe. The left lobe and isthmus were absent and thyroid scans were similar in both cases. The patients were clinically euthyroid. Basal serum thyroid hormones and TSH were within normal range, but TSH response to TRH administration was exaggerated in both patients. The finding of familial occurrence and the same functional and morphological characteristics of remnant thyroid tissue in both cases sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…Although THG has usually been considered sporadic, a report of absence of the right lobe in two sisters strongly suggests a role for an inherited factor (31). In the present study, we found that 9 of the 22 patients, from eight families, had a family history of TD.…”
Section: Familial Factors In Thyroid Hemiagenesissupporting
confidence: 46%
“…Although THG has usually been considered sporadic, a report of absence of the right lobe in two sisters strongly suggests a role for an inherited factor (31). In the present study, we found that 9 of the 22 patients, from eight families, had a family history of TD.…”
Section: Familial Factors In Thyroid Hemiagenesissupporting
confidence: 46%
“…These reports mostly concern adults. A familial incidence has been proposed [16] but this was not investigated in our study.…”
Section: Discussionmentioning
confidence: 78%
“…No significant compensatory growth of the existing lobe in its normal anatomic localization in many patients suggests that the main problem is a lobulation defect rather than a descent disturbance. One aspect seems to be a genetic one, because this rare disorder occurred in monozygotic twins [38], among sisters [39], or together with other thyroid malformations within one family [40,41]. Recently several genes have been found to be involved in thyroid morphogenesis and descent.…”
Section: Discussionmentioning
confidence: 99%